Biochemical pregnancy loss after frozen embryo transfer seems independent of embryo developmental stage and chromosomal status. Issue 3 (September 2018) - Vaiarelli, Alberto; Cimadomo, Danilo; Patrizio, Pasquale; Venturella, Roberta; Orlando, Giovanna; Soscia, Daria; Giancani, Adriano; Capalbo, Antonio; Rienzi, Laura; Ubaldi, Filippo Maria
Abstract: Research question: Biochemical pregnancy loss (BPL), defined as serum beta-human chorionic gonadotropin levels ≥50 IU/l in at least two pregnancy tests, not associated with any ultrasonographical evidence of pregnancy, is often attributed to chromosomal abnormalities; however, no hard evidence exists to support this hypothesis. Are any IVF cycle parameters associated with the occurrence of a BPL? Design: Retrospective study aimed at evaluating the effect of embryo developmental stage at transfer and chromosomal assessment on the BPL rate in IVF after frozen embryo transfer (FET). Specifically, 641 FET of 1179 cleavage stage untested embryos (Group A), 1021 FET of 1259 untested blastocyst stage embryos (Group B), and 789 blastocyst stage FET of 803 euploid embryos (Group C) were performed in a 6-year period. Only FET were evaluated to avoid a potential effect of ovarian stimulation on endometrial receptivity. Results: The BPL rates were similar ( n = 30/217, 13.8% in Group A; n = 37/412, 9.0% in Group B; n = 42/433, 9.7% in Group C). Neither embryo developmental stage at FET nor chromosomal assessment showed a correlation with BPL. Furthermore, logistic regression analyses did not show any association between BPL and patient, cycle and/or transfer characteristics. Conclusions: BPL seems independent of the embryo's developmental stage, the use of trophectoderm biopsy and the chromosomal constitution at FET. Similar BPL rates after transferring euploid blastocysts compared with both untested cleavage and blastocyst stage embryos suggest investigating the role of endometrial and other embryonic factors putatively involved in the process of implantation.